Modern approaches to improving the quality and competitiveness of engineering products through innovation - V. E. Gladkova; V. V. Zharikov; R. V. Zharikov (Путеводитель предпринимателя, 2020)
Article is devoted to modern approaches to providing competitiveness of domestic engineering industry. In article the main tendencies in world and domestic practice are identified and used.